Internet:The Electronic Mobile Library in the Cyberspace - Jas, Nikhil Kumar; Das, Nilay Chandra (Journal of Information and Knowledge, 1999)
Describes Internet and its composition. Traces the history and development of internet. Explains the prerequisites for an access to the Internet world. Different types of Internet connections, domain names and addresses and the facilities offered by various types of service providers in India are discussed. Explains the services available on it. Highlights the status of the Internet in India.